Multi-omics reveals the mechanism of vagus nerve stimulation in the treatment of chronic congestive heart failure - Yuchi Hu; Songyuan Dai; Liling Chen; Xuejuan Ma; Hao Li; Yanan Lu; Chuanxin Li; Xinyun Chen; Hongning Li; Yanzhou Lu; Yimei Huang; Lulu Zhao; et al. (Scientific Reports)
Abstract The potential benefits and underlying mechanisms of Vagus Nerve Stimulation (VNS) in the treatment of Chronic Congestive Heart Failure (CHF) remain insufficiently elucidated. Therefore, this study aims to investigate the therapeutic potential and mechanisms of VNS in treating CHF. In this study, models of CHF and VNS were established prior to performing echocardiography, H&E staining, and flow cytometry to evaluate the effects of VNS on pathological damage associated with CHF and myocardial mitochondrial dysfunction. Multi-omics analysis was conducted to identify changes in metabolites, gut microbiota, and gene expression following VNS treatment. Finally, QPCR was applied to measure levels of essential genes at the mRNA levels. VNS effectively enhances cardiac function, improves metabolic processes, and reduces inflammatory factor levels in dogs with CHF. VNS alleviates myocardial pathological damage, prevents the accumulation of ROS, and increases mitochondrial membrane potential. Multi-omics analysis identified five key metabolites, four key microorganisms, and sixty key genes. Furthermore, combined multi-omics analysis revealed key therapeutic targets, including three metabolites, four microorganisms, and sixteen genes. VNS significantly downregulates the mRNA expression levels of FSTL3, TNFRSF12A, and HBEGF. In summary, VNS has demonstrated effectiveness in the treatment of CHF. Key therapeutic targets identified include Kamahine C, FSTL3, TNFRSF12A, and HBEGF.